2019
DOI: 10.1016/j.tmrv.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Alloimmunization in Transfused Patients With Sickle Cell Disease in Sub-Saharan Africa; a Systematic Review and Meta-Analysis

Abstract: Sickle cell disease (SCD) is the most common monogenic disorder in sub-Saharan Africa (SSA). Blood transfusion to increase the oxygen carrying capacity of blood is vital in the management of many patients with SCD. However, red blood cell (RBC) alloimmunization is a major challenge to transfusions in these patients. Commonly in SSA, pre-transfusion tests only involve ABO D grouping and compatibility without RBC antibody testing. Data on the frequency of RBC alloimmunization in patients with SCD in SSA is limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 58 publications
5
23
1
Order By: Relevance
“…Ngoma et al in a systematic review on the recipients of RBC transfusion of sub‐Saharan Africans noted an alloimmunization rate of 6.7%, and anti‐E was the commonest antibody in the study population [52]. A systematic review and meta‐analysis of alloimmunization of patients with sickle cell disease of sub‐Saharan Africa showed an overall proportion of alloimmunization of 7.4 (95% confidence interval: 5.1–10.0) per 100 transfused patients [53]. Antibodies against E, D, C and K antigens accounted for almost half of antibody specificities in their population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ngoma et al in a systematic review on the recipients of RBC transfusion of sub‐Saharan Africans noted an alloimmunization rate of 6.7%, and anti‐E was the commonest antibody in the study population [52]. A systematic review and meta‐analysis of alloimmunization of patients with sickle cell disease of sub‐Saharan Africa showed an overall proportion of alloimmunization of 7.4 (95% confidence interval: 5.1–10.0) per 100 transfused patients [53]. Antibodies against E, D, C and K antigens accounted for almost half of antibody specificities in their population.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review on rate of alloimmunization in transfusion recipients , a anti-K, anti-C and anti-D Sub-Saharan Africa,Boateng et al (2019) [53] Sickle cell disease 7.40% Anti-E, a anti-D, anti-C and anti-KIran, Darvishi et al (2016) [54] Thalassemia 10% Anti-K, a anti-D and anti-E Iran, Hosseini et al (2020) [55] Patients on regular transfusion 0-55% Anti-K, a anti-E, anti-D, anti-C and anti-c China, Chen et al (2016) [56] Prevalence of unexpected antibodies among Chinese population 0.23% Anti-E, a anti-D, anti-C and anti-c World, Franchini et al (2019) [57] Patients with transfusion dependent thalassemia 11.40% Anti-K, a anti-E, anti-D, anti-c and anti-C Brazil, Gomes et al (2019) [58] Patients with sickle cell disease 28.39% (mean incidence) Rh followed by Kell system Present study (2021) Recipients of RBC transfusion (hospital-based studies) 0.5% Anti-D, a anti-E, anti-c and anti-K Multiply-transfused patients 4.8% Anti-E, a anti-c and anti-K a Most common. on.…”
mentioning
confidence: 99%
“…Anti-Rhesus and anti-Kell specificities were reported by most studies in Africa or developed countries. 21,29 The high immunogenicity of these two systems other than the ABO system could partially explain the high incidence.…”
Section: Risk Factors Occurred Post-transfusion Complicationsmentioning
confidence: 99%
“…In a recent review of transfusion practices in Senegal, 16% of patients were found to have alloantibodies to red blood cells (RBC) and 7.8% had elevated ferritin suggestive of iron overload [23]. A meta-analysis of studies reviewing alloimmunization in Africa identified prevalence rates ranging from 4 to 26% [24]. High rates of either iron overload or alloimmunization would contribute to worse posttransplant outcomes [25].…”
Section: Challenges For Cellular Therapiesmentioning
confidence: 99%